Road to training competences: tsunami and math. (Journal of Parents and Teachers, 2014)
Relevant news, of interest, and mathematical content can be an excellent resource for use in math classes. In this article, we plan to use a 2004 tsunami-based story to perform various tasks with students.
Keywords: Press; news; motivation; didactic idea; mathematics; tsunami.